Effects of a marine diatom Skeletonema costatum extract on Luminescence disease causing Vibrio harveyi during penaeus monodon larviculture (Bangladesh Journal of Botany, 2020)
The crude extract of Skeletonema costatum obtained through cold extraction method was characterized for its phytochemicals, using FTIR and GC-MS. The antagonism of S. costatum extract was tested against Vibrio harveyi, its various virulence factors, and also tested against Vibrio harveyi during Penaeus monodon larviculture. S. costatum extract, controlled the growth of V. harveyi. The zones of inhibition were 12.6 ± 0.2, 6.6 ± 0.1 and 3.7 ± 0.1 mm at 300, 200 and 100 μg, respectively. The production of bio-luminescence was also reduced to 10.0, 11.0, 20.0, 25.0 CPS. The extract contained fatty acids such as 16-octadecanoic acid (48.05%) and pentadecanoic acid (18.94%) as evidenced by GC-MS. S. costatum extract revealed various compounds viz., alcohols, phenols, etc, which are responsible for controlling V. harveyi and virulence factors. During P. monodon larviculture, S. costatum extract at 200 μg/ml showed reduction (p < 0.05) in the cumulative percentage of mortality caused by V. harveyi (35.20 ± 0.6%) as compared to control (76.30 ± 0.8%). It can be concluded that S. costatum extract may be used to control disease-causing V. harveyi during shrimp larviculture.